Parasitic Contamination and Microbiological Quality of Commonly Consumed Fresh Vegetables Marketed in Debre Berhan Town, Ethiopia - Tsegahun Asfaw; Deribew Genetu; Demissew Shenkute; Tassew Tefera Shenkutie; Yosef Eshetie Amare; Berhanu Yitayew (SAGE Publishing, 2023)
Parasitic and microbial contamination and the pattern of occurrence of the parasite species depends on weather conditions, socio-cultural conditions, sampling season, analyzed vegetable products, and other factors. Therefore, local assessment of vegetable contamination is crucial for targeted and effective interventions. A cross-sectional study was conducted from February to August 2022. A questionnaire was used to assess factors associated with parasite contamination of vegetables during the marketing period. The selected vegetables were purchased and processed for parasite and microbial analysis using standard methods. Finally, all data were summarized and analyzed using SPSS software version 25. A total of 180 vegetable samples were purchased from 180 vendors. This study identified a total of 129 parasites from 180 vegetable samples, with an overall contamination rate of (75; 41.7%). Both protozoa (41; 31.8%) and helminthes (88; 68.2%) were identified from vegetables. Contamination with more than one parasite species was (38; 21.1%). The kind of produce, finger nail status of vendors/sellers, the medium of the display, the type of market and not washed prior to display were significantly associated with parasite contamination. The results also showed that vegetable microbial load for total heterotrophic count, total coliform count, fecal coliform count, yeast count, and mold count was higher in the afternoon than in the morning. To decrease risks to public health, local health authorities and/or market inspectors should establish and implement strategies to reduce contamination such as encouraging specific display medium and washing of vegetables prior to display.